Nocturnal blood pressure dipping in acute ischemic stroke. (24th March 2015) - Sargento‐Freitas, J.; Laranjinha, I.; Galego, O.; Rebelo‐Ferreira, A.; Moura, B.; Correia, M.; Silva, F.; Machado, C.; Cordeiro, G.; Cunha, L.
<x xml:space="preserve">Abstract</x> Objectives We aim to assess the impact of early nocturnal blood pressure (BP) variation in the functional outcome of patients after an acute ischemic stroke. Materials and methods We included consecutive stroke patients treated with intravenous thrombolysis (IVrtPA) in a tertiary stroke center. BP measurements were performed at regular intervals throughout day and night during the first 48 h after stroke onset, and subjects were divided into four dipping categories (extreme dippers, dippers, non‐dippers, and reverse dippers). Recanalization was assessed by transcranial color‐coded Doppler and/or angiographic CT. Hemorrhagic transformation was evaluated at 24 h follow‐up CT scan. Functional outcome was evaluated at 3 months after stroke using the modified Rankin Scale. Results A total of 304 patients were included, mean age 72.80 ± 11.10 years. After 24 h of systolic BP monitoring, 30.59% were classified as reverse dippers, 39.14% as non‐dippers, 19.10% as dippers, and 11.18% as extreme dippers. Multivariate analysis did not show an independent association of any dipping class with 3‐month functional outcome. Hemorrhagic transformation was not uniform between dipping classes: 25.81% for reverse dippers, 14.29% for non‐dippers, 15.52% for dippers, and 5.88% for extreme dippers, P = 0.033. Conclusions Nocturnal BP dipping pattern is not associated with functional outcome at 3 months in acute stroke patients treated with IVrtPA. Hemorrhagic transformation was more frequent in reverse dippers.